Modular annular photocatalytic membrane reactor for the degradation of micropollutants: Design and application - Michael S. Leupold; Max Reuschenbach; Gerrit Renner; Anam Asghar; Klaus Kerpen; Lukas Fischer; Torsten C. Schmidt (MethodsX, 2025)
This study presents the Modular Annular Photocatalytic Membrane Reactor (MAPMR), designed to address key challenges in conventional photocatalytic reactors, such as uniform light distribution, efficient photocatalyst recovery, and a precise control over reaction conditions. The MAPMR features: 1) A modular, annular configuration with vertically stacked photocatalyst-immobilized membranes surrounding the light source, ensuring uniform light distribution. 2) Continuous separation and recovery of photocatalysts, while providing precise control over parameters such as reaction time, temperature, and light intensity. 3) Use of UV-cut filters to block light wavelength below specific thresholds.The reactor was tested with TiO₂-decorated polyethersulfone (PES) membranes (TiO₂-PES) and equipped with selective UV cut-off filters to selectively assess individual micropollutant degradation processes. These filters block wavelengths below 296 nm, 325 nm, and 405 nm, facilitating separate studies of UV- and visible light-driven photocatalysis while preventing direct photolysis. The reactor's modular design facilitates easy membrane replacement, supports diverse operational modes, and integrates in-line and on-line monitoring for real-time analytical insights. Amoxicillin (AMX), a model organic pollutant, was used as the probe compound to evaluate reactor performance with potassium nitrate as a UV cut-off filter (λ < 325 nm) providing precise evaluation of both photocatalytic and photolytic AMX degradation.